On the link of global warming and cloudiness in mid hills of Himachal Himalayas, India - Mohan Singh Jangra; Priyanka Jattan; S.K. Bhardwaj; Purnima Mehta (International Journal of Climate Conditions, 2026)
The present study investigated the monthly, seasonal, and annual cloud cover variability over two stations in the mid hills sub-temperate subhumid zone of Himachal Pradesh, by using Pearson’s correlation coefficient, Mann-Kendall (MK), and Sen’s slope estimator test. Daily data on cloud cover, sunshine hours, maximum and minimum temperature, morning and evening relative humidity, evaporation and rainfall for the period of 22 years (2001–2022) were used in the investigation. In the study, we have tried to analyze the trends in cloud cover and their relationship with bright sunshine, temperature, and other climatic variables under changing climatic scenarios. Both the stations showed an increasing trend in cloudiness, which was increasing at a non-significant rate of 0.01 Okta/year at Solan and 0.30 Okta/year at Kullu. From –0.64 to –0.87, a significant inverse correlation was observed between cloud cover and sunshine hours. It was negatively correlated with maximum temperature and ranged from-0.03 to-0.42 and evaporation with an r value that ranged from-0.08 to-0.44. The minimum temperature showed a significant positive correlation with cloud cover at Kullu but a non-significant positive correlation at Solan. Rainfall showed a negative correlation at Solan whereas a positive correlation was found at Kullu as the total cloudiness and its increasing rate were higher at Kullu. The overall trend in cloud cover in the study area was significantly increasing (Z = 1.66) with an upward magnitude (Q = 0.03). We tried a case study to work out a local trend in cloud cover, which may be extended over time and space to reach some conclusions.
Keywords: Cloudiness; Himachal Himalayas; Trend analysis; weather variables, correlation